Acetylcholine receptor antibody-positive myasthenia gravis associated with small-cell lung cancer: A case report. Issue 17 (April 2018) - Yamasaki, Masahiro; Funaishi, Kunihiko; Saito, Naomi; Yonekawa, Tomomi; Yamawaki, Takemori; Ihara, Daisuke; Daido, Wakako; Ishiyama, Sayaka; Deguchi, Naoko; Taniwaki, Masaya; Hattori, Noboru
Abstract: Rationale: Only few cases of myasthenia gravis (MG) associated with small-cell lung cancer (SCLC) have been reported, and cases positive for acetylcholine receptor antibody (AChR-ab) are even rarer. The efficacy of standard MG treatment, such as cholinesterase inhibitor therapy, immunosuppressive therapy using steroids and immunosuppressive drugs, plasma exchange, and intravenous immune globulin (IVIg), for these cases is unclear. Patient concerns and diagnoses: A 71-year-old man complained of bilateral eyelid ptosis. He also presented with dysphagia and masticatory muscle fatigue after chewing. The edrophonium test was positive, and the serum AChR-ab level was increased; therefore, the patient was diagnosed with MG. Computed tomography scan showed a nodule on the left upper lobe of the lung and mediastinal lymphadenopathy. Further examination revealed the lesion as SCLC. Finally, he was diagnosed with AChR-ab-positive MG associated with SCLC. Interventions and outcomes: Oral pyridostigmine and tacrolimus were administered to treat MG; however, his symptoms worsened. Therefore, methylprednisolone and IVIg were administrated, which temporarily improved his symptoms. However, they remained uncontrolled. Meanwhile, chemotherapy with carboplatin and etoposide was administered to treat his SCLC. The lesions shrunk, and the MG symptoms and serum AChR-ab level also improved. Lessons: AChR-ab-positive MG may develop as a comorbidity of SCLC. In such cases, management might require treatment for SCLC in addition to the standard MG treatment to stabilize the MG symptoms.